Viabilitas Benih Dan Vigor Bibit Mangga Kweni (Mangifera Odorata Griff.) Dari Berbagai Sumber Benih Terpilih Dari Desa Bente Kecamatan bungku Tengah Kabupaten Morowali - Moh. Hatta; Enny Adelina; Nuraeni Nuraeni (Universitas Tadulako, 2018)
ABSTRACT The aim of this research was to find high seed viability and vigor of Kweni manggo selected from various seed sources in Bente village, Central Bungku sub district, Morowali district. The research was conducted from April to July 2017 at the Seed Science and Technology Laboratory, and at the Academic Garden of the Agriculture Faculty of Tadulako University, Palu. This study used a one factorial completely randomized design with the seed sources as its factor. The seeds were obtained from trees grown at different sites i.e. Bente village 1, Bente village 3 and Bente village 14. The seeds were then tested for their vigor using a randomized block design method grouped by the tree height. The results showed that the seed viability and vigor obtained from the Bente 14 parent trees are higher than those from the other sources in Bente village, Central Bungku d sub district, Morowali district. Keyword: Manggo, sources of seed, viability, vigour.